Spatio-temporal description of the cavitating flow behavior around NACA 2412 hydrofoil. (November 2015) - Rudolf, P; Štefan, D; Sedlář, M; Kozák, J; Habán, V; Huzlík, R
Abstract: Spatio-temporal description of the cavitating flow around hydrofoil with 8 degrees incidence using proper orthogonal decomposition (POD) is presented. POD is a suitable tool, which provides information not only about the flow dynamics, but also about relevance of different flow structures. POD also enables to track energy transport within the domain and energy transfer among the eigenmodes of the flow field. Analysis documents change of the flow structure for decreasing cavitation number, which can be most likely attributed to sheet/cloud cavitation transition.